Some epidemiological observations on medicinal and non-medicinal poisoning in preschool children. Issue 3 (June 1992) - Ferguson, J A; Sellar, C; Goldacre, M J
Abstract : STUDY OBJECTIVE--The aim was to identify and compare rates of admission to hospital of preschool children for medicinal and non-medicinal poisoning in a defined population. DESIGN--The study was an analysis of computerised abstracts of hospital inpatient records for poisoning. SETTING--Six districts in southern England covered by the Oxford record linkage study. SUBJECTS--The subjects were children under six years of age residing in the six districts from 1975 to 1986. MEASUREMENTS AND MAIN RESULTS--6152 children, drawn from an average annual resident population of 164, 000 children in 1975-1986, experienced 6562 hospital admissions for poisoning before six years; 3702 (56.4%) were attributed to medicinal and 2860 (43.6%) to non-medicinal agents. Of the latter, 646 (9.8% of the total) were recorded under the International classification of diseases code, described as "noxious food" (almost exclusively plant material). Average annual admission rates in children under six were 1.88 per 1000 for medicinal agents and 1.45 for non-medicinal substances. Analgesics accounted for 28.1% of the admissions for medicinal poisoning; berries and mushrooms for 97.4% of the plant materials; and corrosive aromatics, acids and alkalis for 22.0% of the other non-medicinals. Admission rates were higher in males than females in each category of poisoning. In children aged 1-4 years there was a significant decrease in admission rates between 1975 and 1986, averaging per annum 5.8% for medicinal poisoning, 6.9% for non-medicinal poisoning (excluding plant material), and 12.8% for plant material poisoning. Significant seasonal variation was found for each class of poisoning. CONCLUSIONS--Admission rates for medicinal and non-medicinal poisoning in preschool children declined between 1975 and 1986. The decline could reflect a change in thresholds for admission although, if so, this would be against the general trend in paediatric medical admissions, which is upward. An alternative explanation is a decline in the incidence of poisoning.